Mixed Invasive Ductal and Lobular Carcinoma of the Breast: Prognosis and the Importance of Histologic Grade. (5th December 2018) - Metzger‐Filho, Otto; Ferreira, Arlindo R.; Jeselsohn, Rinath; Barry, William T.; Dillon, Deborah A.; Brock, Jane E.; Vaz‐Luis, Ines; Hughes, Melissa E.; Winer, Eric P.; Lin, Nancy U.
Abstract: Background: The diagnosis of mixed invasive ductal and lobular carcinoma (IDC‐L) in clinical practice is often associated with uncertainty related to its prognosis and response to systemic therapies. With the increasing recognition of invasive lobular carcinoma (ILC) as a distinct disease subtype, questions surrounding IDC‐L become even more relevant. In this study, we took advantage of a detailed clinical database to compare IDC‐L and ILC regarding clinicopathologic and treatment characteristics, prognostic power of histologic grade, and survival outcomes. Materials and Methods: In this retrospective cohort study, we identified 811 patients diagnosed with early‐stage breast cancer with IDC‐L or ILC. Descriptive statistics were performed to compare baseline clinicopathologic characteristics and treatments. Survival rates were subsequently analyzed using the Kaplan–Meier method and compared using the Cox proportional hazards model. Results: Patients with ILC had more commonly multifocal disease, low to intermediate histologic grade, and HER2‐negative disease. Histologic grade was prognostic for patients with IDC‐L but had no significant discriminatory power in patients with ILC. Among postmenopausal women, those with IDC‐L had significantly better outcomes when compared with those with ILC: disease‐free survival (DFS) and overall survival (OS; adjusted hazard ratio [HR], 0.54; 95% confidence interval [CI] 0.31–0.95). Finally, postmenopausal women treated with an aromatase inhibitor had more favorable DFS and OS than those treated with tamoxifen only (OS adjusted HR, 0.50; 95% CI, 0.29–0.87), which was similar for both histologic types ( p = .212). Conclusion: IDC‐L tumors have a better prognosis than ILC tumors, particularly among postmenopausal women. Histologic grade is an important prognostic factor in IDC‐L but not in ILC. Abstract : In this retrospective analysis, a large, detailed, and curated single center database was used to compare clinicopathologic features and outcomes between invasive lobular carcinoma and mixed invasive ductal and lobular carcinomas, focusing on the prognostic implications of histological grade and taking into consideration the differences in systemic therapies.